2014
DOI: 10.1021/jp5010659
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical In(OH)3 as a Precursor to Mesoporous In2O3 Nanocubes: A Facile Synthesis Route, Mechanism of Self-Assembly, and Enhanced Sensing Response toward Hydrogen

Abstract: Mesoporous In 2 O 3 nanocubes were achieved in this present work following a transformation from hierarchical structures of mesoporous In(OH) 3 nanocubes synthesized hydrothermally. Appreciable control on the morphology of In(OH) 3 nanostructures was attained by optimizing the reactant concentration, ratio of structure directing agent in the reaction medium (water/PEG ratio), the reaction temperature, and time. The synthesized samples were characterized extensively by XRD, TG-DTA, micro-Raman, and UV-DRS. Surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 87 publications
5
51
0
Order By: Relevance
“…7) indicate that they both have pure monoclinic phase of Bi 2 O 3 (JCPDS 41-1449). General, polyethylene glycol (PEG) is a nonionic surfactant with uniform and ordered chain structure and easily adsorbed on different crystal faces to confine the growth rate of crystal in some certain directions which leads into anisotropic growth of crystals during material synthesis [34][35][36][37][38]. In this reaction, the uniform and ordered chains of PEG play a crucial role not only in the morphology, even more important in phase-transition of Bi 2 O 3 .…”
Section: Phase-transitionmentioning
confidence: 99%
“…7) indicate that they both have pure monoclinic phase of Bi 2 O 3 (JCPDS 41-1449). General, polyethylene glycol (PEG) is a nonionic surfactant with uniform and ordered chain structure and easily adsorbed on different crystal faces to confine the growth rate of crystal in some certain directions which leads into anisotropic growth of crystals during material synthesis [34][35][36][37][38]. In this reaction, the uniform and ordered chains of PEG play a crucial role not only in the morphology, even more important in phase-transition of Bi 2 O 3 .…”
Section: Phase-transitionmentioning
confidence: 99%
“…Thus, porous micro-/nanostructures can cause the enhancement of both sensing sensitivity and response rate [22]. For obtaining porous In 2 O 3 , one method is through precursor-mediated route [23][24][25]. In this case, In(OH) 3 [26], InOOH [27,28], or similar precursors were firstly prepared.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lee et al demonstrated the synthesis of porous In 2 O 3 hollow spheres through a sucrose-mediated precursor [29]. Mesoporous In 2 O 3 nanocubes were prepared from hierarchical In(OH) 3 nanocubes synthesized hydrothermally [23]. Recently, Zhang et al synthesized porous In 2 O 3 micro-/nanoflowers from In(OH) 3 precursor.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs are ideal templates to synthesize quasi-1D metal oxides, because of their excellent acid and alkali resistance. [27][28][29][30][31] Pd-loaded In 2 O 3 may theoretically improve sensing performance. In earlier studies, Ning Du et al 21 prepared porous In 2 O 3 nanotubes with polyelectrolytes using layer-by-layer assembly/deposition on CNTs, followed by calcination.…”
Section: Introductionmentioning
confidence: 99%